School organizational factors as predictors of student achievement: Principals perspective - Otara, Alfred; Omolo, Hezekiah Otieno (International Journal for Educational and Vocational Studies, 2021)
This study aimed to deepen our understanding of how school organization factors can be used to predict students academic performance. In particular, factors examined were leadership skills, nature of students, parental involvement and the school environment. Using stratified and simple random sampling, a total of 152 principals were selected for the study. A survey questionnaire was used to collect data whose variance and regression was analyzed using ANOVA. The findings consolidate the importance of leadership skills, nature of students, learning environment and parents in predicting students learning success. All the four aspects of school organization contributed differently to predicting students academic performance with the Principals' Leadership Skills having the highest impact while parental involvement made the least contribution. Findings of this study are important to educational administrators to ensure a supportive learning environment for the students. In addition education authorities both at national and local levels should enhance field inspections to rate the learning atmosphere. The study also serves to contribute to the body of knowledge on school organizational factors in addition to triggering the need for more research in this domain.